Eye(I) Still Know! – An App for the Blind Built using Web and AI - Akshata Sangwai; Shriya Deshmukh; Vardaan Sathe; Rishika Agarwal; Rakhi Kalantri (International Journal of Engineering and Management Research, 2021)
This paper proposes eye(I) still know!, a voice control solution for the visually impaired people. The main purpose is even though the blind cannot see they can still know where to go and what to do! Nearby 60% of total blind population across the world is present in India. In a time where no one likes to rely on anyone, this is a small effort to make the blind independent individuals. This can be achieved using wireless communication, voice recognition and image scanning. The application with the use of object identification will priorly inform about the barriers in the path. The software will use the camera of the device and scan all the obstacles with their corresponding distances from the user. This will be followed by audio instructions through audio output of the device. This will efficiently direct the user through his/her way.